The biology, ecology and conservation of euphorbia groenewaldii : an endangered succulent of the Limpopo Province - Van Tonder, Rowan Conrad (University of Limpopo (Turfloop Campus), 2012)
Several South African Euphorbia species are threatened with extinction, yet only a few have been studied in sufficient detail to develop a conservation management plan based on sound scientific principles. The focus of this study was on one of the highly threatened dwarf Euphorbias, namely Euphorbia groenewaldii. Apart from a report on the species distribution and estimated population numbers by Raal (1986), virtually nothing is known about this attractive succulent species. Conservation and management of threatened species requires a thorough understanding of their biology, ecological requirements and spatial distribution which should form the basis of a monitoring programme that must be conducted at regular intervals. Euphorbia groenewaldii is endemic to six rocky schist and quartzite ridges in the vicinity of Polokwane, the capital of South Africa’s Limpopo Province. The species’ small global range, small number of populations and small population sizes in some instances, render the species susceptible to anthropogenic and environmental stochasticity. Biotic and abiotic features were investigated to determine their influences, as well as, the threats (trampling, anthills, herbivory and number of senescent plants) facing Euphorbia groenewaldii. Canopy area was used to determine the stage (age) and size structure of each population. Biotic features and natural environmental components considered were percentage cover of grass, forbs, dead vegetation, stones, fixed rock and bare ground. The percentage cover, of all the biotic features (grass, forbs and dead material) and environmental components (stones, fixed rock and bare ground), most preferred by E. groenewaldii is close to 25% in the direct vicinity of the individual plant. Euphorbia groenewaldii select areas with fixed rock more than in any other biotic feature or environmental component. This could be for protection from, or a result of, trampling by large herbivores, or that it’s most preferred mineral substance is found within this geology. Abiotic features considered in this study were; fire, aspect, slope degree, slope position and soil. The E. groenewaldii population as a whole prefers to grow on the northern aspects. Furthermore, with threats affecting all the populations, it is forced to grow in the middle of steeper slopes. Currently the only fire ‘regime’ is a natural or accidental occurring fire. The area where E. groenewaldii grows belongs to the local government and is open to public traffic. If a regular (once a year) cold-fire regime for E. groenewaldii can be put in place and, if possible, coincide with rainfall events it could help the release of more seeds and help with a more constant rate of seedling recruitment for this species. Such a fire event was witnessed during the study period and subsequent new growth and seedling appearances were recorded. Threats that were noted and considered were mostly of a biotic nature (absence of fire being the exception) and included trampling, herbivory and termite mounds. Other threats not included are urban expansion and mining/quarrying activities. These types of threats are real and more extensive, and if not monitored could completely destroy a population in a very short time period. Trampling is a significant threat facing this species, particularly at the Melkboomfontein population, where 31% of the population shows physical signs of trampling by livestock; mainly cattle. Herbivory is also a threat to E. groenewaldii and causes significant damage (15% over the total population according to the statistical analysis). There is also a significant difference in the effect anthills have on E. groenewaldii as opposed to the other threats, which have almost no effect on its population size. In addition to the above, surveys were conducted to determine the species’ present extent of occurrence and area of occupancy to obtain population size estimates and densities. The results were compared with data of a study by Raal in 1986. The results of this study showed a dramatic decline in population numbers. Possible reasons for the reduction include habitat loss, better survey techniques (that provided better predictions of population density) and a more comprehensive survey and data analysis in this study, and a failure to implement the conservation management plan proposed by Raal (1986). It is estimated that the total number of individuals in all the populations comprise approximately 26 500 individual plants, with all occurring in an area of less than 4 km2 (excluding the Dalmada populations). The small extent of occurrence suggests that E. groenewaldii populations require urgent protection. An investigation of morphological differences between E. groenewaldii and E. tortirama was conducted. This investigation attempted to find external morphological differences by looking at the flower peduncles, colour of bracts and spine shields. Analysis of these data showed differences in the length of the peduncles (longer in E. groenewaldii than in E. tortirama); colour of bracts (colourless in E. groenewaldii as opposed to the reddish-pink bracts of E. tortirama) and the continuation (E. groenewaldii) and non-continuation (E. tortirama) of spine shields. In 1986, Euphorbia groenewaldii’s conservation status was considered endangered; it is still the case today. However, the IUCN status of E. groenewaldii was reevaluated on the current data gathered, which has placed E. groenewaldii in the Critically Endangered category. This is mainly due to the small extent of occurrence (approximately 4 km2) of the species (less than the 100 km2 which according to the IUCN Redlist Categories and Criteria, 2006, criteria B, classifies species as critically endangered).
Thesis (M.A. (Botany)) --University of Limpopo, 2012
Keywords: Euphorbia; Euphorbia groenewaldii; 583.69; Euphorbia; Tree spurge